Replacement of a photomultiplier tube in a 2-inch thallium-doped sodium iodide gamma spectrometer with silicon photomultipliers and a light guide - Kim, Chankyu; Kim, Hyoungtaek; Kim, Jongyul; Lee, Chaehun; Yoo, Hyunjun; Kang, Dong Uk; Cho, Minsik; Kim, Myung Soo; Lee, Daehee; Kim, Yewon; Lim, Kyung Taek; Yang, Shiyoung; et al. (Nuclear engineering and technology, 2015)
The thallium-doped sodium iodide [NaI(Tl)] scintillation detector is preferred as a gamma spectrometer in many fields because of its general advantages. A silicon photomultiplier (SiPM) has recently been developed and its application area has been expanded as an alternative to photomultiplier tubes (PMTs). It has merits such as a low operating voltage, compact size, cheap production cost, and magnetic resonance compatibility. In this study, an array of SiPMs is used to develop an NaI(Tl) gamma spectrometer. To maintain detection efficiency, a commercial NaI(Tl) 2′ × 2′ scintillator is used, and a light guide is used for the transport and collection of generated photons from the scintillator to the SiPMs without loss. The test light guides were fabricated with polymethyl methacrylate and reflective materials. The gamma spectrometer systems were set up and included light guides. Through a series of measurements, the characteristics of the light guides and the proposed gamma spectrometer were evaluated. Simulation of the light collection was accomplished using the DETECT 97 code (A. Levin, E. Hoskinson, and C. Moison, University of Michigan, USA) to analyze the measurement results. The system, which included SiPMs and the light guide, achieved 14.11% full width at half maximum energy resolution at 662 keV.